2008
DOI: 10.1007/s10072-008-1021-3
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline in the treatment of depressive disorders in patients with Parkinson’s disease

Abstract: We studied 54 idiopathic Parkinson's disease (PD) patients with depressive disorders (DD) to compare the efficacy and the effect of treatment with sertraline in the usual formulation and in the liquid oral concentrate (LOC) formulation. After 6 months of sertraline treatment, the Hamilton Depression Rating Scale and the Montgomery and Asberg Depression Rating Scale showed a decrement (p<0.001, for both formulations). Parkinson's Disease Questionnaire scores improved (p<0.005 for usual formulation and p<0.001 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…In a 6-month open-label, randomised trial, sertraline liquid formulation was compared to sertraline regular formulation in 54 depressed PD patients [307]. Both formulations were equally effective at improving the Turkish-HDRS and Turkish-MADRS scores.…”
Section: Sert Inhibitorsmentioning
confidence: 99%
“…In a 6-month open-label, randomised trial, sertraline liquid formulation was compared to sertraline regular formulation in 54 depressed PD patients [307]. Both formulations were equally effective at improving the Turkish-HDRS and Turkish-MADRS scores.…”
Section: Sert Inhibitorsmentioning
confidence: 99%
“…19,39,50,51 Sertraline liquid oral concentrate may also be a useful treatment for depression in patients with PD, especially for those who have difficulty swallowing. 52 Citalopram. One double-blind, randomized, placebo-controlled study and two open-label studies have suggested that citalopram has beneficial effects in treating depression in patients with PD, with a good tolerability profile.…”
Section: Selective Serotonin Reuptake Inhibitors (Ssris)mentioning
confidence: 99%
“…14 However, recent data have shown that antidepressant use in PD has rendered motor impairment either unchanged [15][16][17][18][19] or significantly improved, 20 as measured by the motor portion of the Unified Parkinson's Disease Rating Scale. A previous study by Sclar et al, which assessed US physician office-based care provided to patients with PD from 1990 to 1995, found that depression was diagnosed in only 4.1% of physician office visits.…”
Section: Introductionmentioning
confidence: 99%